The American Academy of Health Behavior 2018 Annual Scientific Meeting: "An Equity Approach to Health Behavior Innovations" - M. Renée Umstattd Meyer (New Prairie Press, 2018)
The American Academy of Health Behavior (AAHB) hosted its 18th Annual Scientific Meeting at the Embassy Suites by Hilton in historic downtown Portland, OR March 4-7, 2018. The meeting's theme was "An Equity Approach to Health Behavior Innovations." This publication describes the meeting theme and includes the refereed abstracts presented at the 2018 Annual Scientific Meeting.